Workshop: Creating Diagrams for Teaching Materials with Microsoft Visio (Revista Electrónica Calidad en la Educación Superior, 2025)
This paper presents the systematization of the implementation of the Workshop on Creating Outlines for Teaching Materials with Microsoft Visio, offered by the Distance Education Center at the State Distance Education University since 2022, as it contributes to the didactic mediation of written materials. A mixed methodology was used; based on the results of the initial and final assessments applied to three workshop offerings, complemented by the final evaluations, it is concluded that the workshop has contributed to teacher training in the use of Microsoft Visio for content mediation. It is recommended that the manual for installing the program be improved, as well as that a study be conducted on the software's use after the workshop is approved.
Keywords: didactic mediation; Microsoft Visio; universal design for learning; teaching material; workshop